CTA534 : Intermediate 3D computer animation / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course is an extension of Digital Animation Technology course which provides the indepth on character animation and rigging. Students will experience the character animation skills of building a skeletal structure for keyframe animation of the 3D model through the understanding and application of the principles of animation